2014
DOI: 10.1002/oby.20940
|View full text |Cite
|
Sign up to set email alerts
|

Association between metabolic deteriorations and prior gestational diabetes according to weight status

Abstract: Objective: The aim of the present study is to investigate the effect of prior gestational diabetes mellitus (GDM) on glucose and insulin homeostasis according to weight status. Methods: The analysis included 299 women, 216 with [GDM(1)] and 83 without prior GDM [GDM(2)]. The mean time between pregnancy and testing was 3.9 years. Glucose values were obtained from a 2-h 75 g oral glucose tolerance test (OGTT). Body composition was measured by dual-energy X-ray. Results: In women with normal BMI, fasting glucose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The 20 studies included in this systematic review and meta-analysis had differing lengths of follow-up, time of screening, ethnic origin of study participants, and diagnostic criteria for both GDM and T2DM 2728313334353637383940414243444546474849. All studies were observational, seven were described as prospective cohorts, six as retrospective cohorts, four as population based studies, two as follow-up studies, and one as a hospital based study.…”
Section: Resultsmentioning
confidence: 99%
“…The 20 studies included in this systematic review and meta-analysis had differing lengths of follow-up, time of screening, ethnic origin of study participants, and diagnostic criteria for both GDM and T2DM 2728313334353637383940414243444546474849. All studies were observational, seven were described as prospective cohorts, six as retrospective cohorts, four as population based studies, two as follow-up studies, and one as a hospital based study.…”
Section: Resultsmentioning
confidence: 99%
“…Mothers who had a pregnancy complicated or not complicated by GDM between 2003 and 2013 were recruited, as well as their children. They were recruited through invitation letters sent to women with a diagnosis of GDM according to medical records of the two major hospitals with a neonatal care unit in the metropolitan area of Quebec City ( Hôpital Saint‐François d'Assise, Centre Hospitalier de l'Université Laval – CHUL ) or according to administrative data from the provincial health plan registry ( Régie de l'assurance maladie du Québec ) . Recruitment was also conducted by emails sent to Laval University community as well as posts on Facebook and healthcare websites.…”
Section: Methodsmentioning
confidence: 99%
“…Our initial search yielded 7970 publications, of which 109 articles were reviewed in full and 43 studies were included in the final analysis [3,11,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55]. Forty studies reported on T2DM [3,11,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43…”
Section: Resultsmentioning
confidence: 99%